2008
DOI: 10.1074/jbc.m804537200
|View full text |Cite
|
Sign up to set email alerts
|

Joint Requirement for Rac and ERK Activities Underlies the Mid-G1 Phase Induction of Cyclin D1 and S Phase Entry in Both Epithelial and Mesenchymal Cells

Abstract: Cyclin D1 gene induction is a key event in G1 phase progression. Our previous studies indicated that signaling to cyclin D1 is cell type-dependent because the timing of cyclin D1 gene expression in MCF10A mammary epithelial cells and mesenchymal cells such as fibroblasts and vascular smooth muscle cells is very different, with epithelial cells first expressing cyclin D1 in early rather than mid-G1 phase. In this report, we induced a mesenchymal phenotype in MCF10A cells by long-term exposure to TGF-␤ and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Accordingly, restriction of FOXM1 expression by siRNA, in the HuH6 cell line, led to G 2 –M phase arrest. FOXM1 inhibition was also associated with G 0 –G 1 arrest which could depend on modulation of the activity of FOXM1 targets, including pERK1/2 downregulation,36 and possible activation of G 1 inhibitors such as p21 WAF1 and p27 KIP1 1417. Thus, the present investigation shows FOXM1 regulation by genes controlling the susceptibility to HCC, and underlines the role of uncontrolled progression through the cell cycle as an effector mechanism of these genes, determining the susceptible phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…Accordingly, restriction of FOXM1 expression by siRNA, in the HuH6 cell line, led to G 2 –M phase arrest. FOXM1 inhibition was also associated with G 0 –G 1 arrest which could depend on modulation of the activity of FOXM1 targets, including pERK1/2 downregulation,36 and possible activation of G 1 inhibitors such as p21 WAF1 and p27 KIP1 1417. Thus, the present investigation shows FOXM1 regulation by genes controlling the susceptibility to HCC, and underlines the role of uncontrolled progression through the cell cycle as an effector mechanism of these genes, determining the susceptible phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…108 An alternative splice variant of Rac1, Rac1b, which encodes a highly active isoform, was also increased in colon cancer. 109 Rather than changes at the protein level, the activity of another isoform of Rac, Rac3, was found ERK-independent cyclin D1 expression was not seen in mesenchymal cells (and was not sufficient to induce Rb phosphorylation or S-phase entry), but the mid-G 1 induction is conserved in both epithelial and mesenchymal cells, 88 highlighting the potential differences in Rac-dependent cell cycle events in different cell types.…”
Section: In Vivo Evidence Implicating Rac Signaling In Tumorigenesismentioning
confidence: 99%
“…87 A more recent study using MCF10A cells confirmed that Rac can induce cyclin D1 in early G 1 independently of ERK, but also showed that mid-G 1 phase induction of cyclin D1 required parallel signaling from both ERK and Rac. 88 Interestingly, the early many opportunities to develop novel therapeutic strategies to target Rac signaling at different stages of tumor cell metastasis.…”
Section: Rac Signaling In G 1 /S Phase Of the Cell Cyclementioning
confidence: 99%
“…Both cell-cell and cell-matrix adhesion signal to increase cyclin D1 levels for progression through the cell cycle and Rac1, together with ERK regulates this (Fournier et al , 2008; Klein et al , 2008). Rac1 is tightly regulated in cytokinesis, both temporally and spatially and is inhibited at the cleavage furrow by centralspindlin, a GTPase activator (GAP) (Canman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%